Electrolyte, secondary battery, and electric device

CN116895834BActive Publication Date: 2026-10-23SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310859138.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2026-10-23
Estimated Expiration
2043-07-12

AI Technical Summary

Technical Problem

[0005]本发明所要解决的技术问题是提供一种电解液、二次电池及用电设备,以解决现有锂离子电池在低温场景下容易出现析锂、极化、电极处钝化膜阻抗较高的问题

Benefits of technology

[0022]本发明实施例中,所提供的电解液包括具有式(A)化合物,式(A)中具有烷氧基、氮原子及二氧杂环戊基;其中,烷氧基结构有助于(A)化合物和锂离子之间进行配位,从而调节锂离子的溶剂化结构,改变界面传递阻抗;胺基中N杂原子则有助于负极侧形成高锂离子通过能力的界面膜,提高负极的离子传输能力,有力改善其在快充和低温场景中的应用性能;而二氧杂环戊基更容易发生开环反应;因此,(A)化合物的加入可以分别在正极和负极表面形成阻抗小且稳定的钝化膜,抑制界面阻抗增加及电解液分解,从而提高电池低温循环的稳定性,因而解决了现有锂离子电池在低温场景下容易出现析锂、极化、电极处钝化膜阻抗较高的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The embodiment of the present application provides an electrolyte, a secondary battery and an electric equipment, wherein the electrolyte provided by the embodiment of the present application comprises a compound with formula (A), the compound with formula (A) has alkoxy, a nitrogen atom and dioxolane, the addition of formula (A) can form a stable passivation film with small impedance on the surface of a positive electrode and a negative electrode respectively, the increase of interface impedance and the decomposition of electrolyte are inhibited, so that the stability of low-temperature cycle of the battery is improved, and thus the problems that lithium ion batteries in the prior art are prone to lithium precipitation, polarization and high impedance of the passivation film at the electrode under a low-temperature scene are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery manufacturing technology, and in particular to an electrolyte, a secondary battery, and an electrical device. Background Technology

[0002] Currently, secondary batteries, especially lithium-ion batteries, are widely used in various fields due to their numerous advantages such as long cycle life, high energy density, short charging time, small size, light weight, and no memory effect.

[0003] The electrochemical performance and safety of lithium-ion batteries are both affected by the electrolyte. The electrolyte not only determines the electrochemical window and energy density of the battery, but also regulates the properties of the electrode / electrolyte interface.

[0004] However, existing lithium-ion batteries are prone to problems such as lithium plating, polarization, and high passivation film impedance at the electrodes in low-temperature scenarios, which seriously affect the low-temperature cycle performance of the battery. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide an electrolyte, a secondary battery and an electrical device to solve the problems of lithium plating, polarization and high passivation film impedance at the electrodes that are prone to occur in existing lithium-ion batteries at low temperatures.

[0006] To solve the above problems, the present invention is achieved through the following technical solution:

[0007] This invention proposes an electrolyte comprising a compound of formula (A):

[0008]

[0009] Wherein, R1, R2, and R3 each independently contain at least one of hydrogen, a substituted or unsubstituted C1-C10 alkyl group, a substituted or unsubstituted C1-C10 ester group, a substituted or unsubstituted pyrimidinyl group, or a substituted or unsubstituted triazolopyrimidinyl group;

[0010] The substituted group comprises at least one of hydroxyl, phenyl, amino, halogen, alkylthio, siloxane, and fluorobenzene-substituted cyclopropane.

[0011] Furthermore, in the electrolyte, the compound of formula (A) contains at least one of formulas (A1) to (A9):

[0012]

[0013] Furthermore, based on the total mass of the electrolyte, the mass percentage of the compound of formula (A) is 0.01% to 5%.

[0014] Furthermore, based on the total mass of the electrolyte, the mass percentage of the compound of formula (A) is 0.05% to 3%.

[0015] Furthermore, the electrolyte also includes at least one of vinylene carbonate, fluorovinyl carbonate, 1,3-propenesulfonate lactone, and 1,3-propanesulfonate lactone.

[0016] The present invention also proposes a secondary battery, which includes a positive electrode, a negative electrode, and an electrolyte as described above.

[0017] Furthermore, the positive electrode sheet includes a positive electrode active material, which includes a nickel-cobalt-manganese material, and the nickel-cobalt-manganese material includes Li a Ni x Co y Mn z M e O2, wherein 0.9≤a≤1.1, 0≤e≤0.1, 0.3≤x<1.0, 0<y<0.4, 0.1<z<0.4, x+y+z=1.0, and M contains at least one of Al, Zr, Sr, Ti, B, Mg, Sn, W, Y, Ba, Nb, Mo, Ta, Si, La, Er, Nd, Gd, and Ce.

[0018] Furthermore, in the secondary battery, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector, wherein the compaction density of the positive active material layer is 1.6 g / cm³. 3 ~2.8g / cm 3 .

[0019] Furthermore, in the aforementioned secondary battery, the areal density of the positive electrode active material layer is 260 g / m². 2 ~330g / m 2 .

[0020] The present invention also proposes an electrical device, wherein the aforementioned secondary battery is provided, and the secondary battery serves as the power supply for the electrical device.

[0021] Compared with the prior art, the embodiments of the present invention have the following advantages:

[0022] In this embodiment of the invention, the electrolyte provided includes a compound of formula (A), which contains an alkoxy group, a nitrogen atom, and a dioxacyclopentyl group. The alkoxy group facilitates coordination between the compound (A) and lithium ions, thereby regulating the solvation structure of lithium ions and altering the interfacial transport impedance. The nitrogen atom in the amine group helps form a high lithium-ion permeability interfacial film on the negative electrode side, improving the ion transport capability of the negative electrode and significantly enhancing its performance in fast charging and low-temperature scenarios. The dioxacyclopentyl group is more prone to ring-opening reactions. Therefore, the addition of compound (A) can form low-impedance and stable passivation films on the surfaces of the positive and negative electrodes, respectively, suppressing the increase in interfacial impedance and electrolyte decomposition, thereby improving the stability of the battery during low-temperature cycling. This solves the problems of lithium plating, polarization, and high passivation film impedance at the electrodes that are common in existing lithium-ion batteries under low-temperature conditions.

[0023] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and do not limit this application. Detailed Implementation

[0024] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to specific embodiments.

[0025] The applicant of this invention has discovered that although lithium-ion batteries have been widely used in various fields due to their many advantages such as long cycle life, high energy density, short charging time, small size, light weight, and no memory effect, the electrode / electrolyte interface of existing lithium-ion batteries is unstable. In low-temperature scenarios, problems such as lithium plating, polarization, and high impedance of passivation film at the electrode are prone to occur, which seriously affect the low-temperature cycle performance and fast charging performance of the battery.

[0026] To address the aforementioned problems, this invention provides an electrolyte comprising a compound of formula (A):

[0027]

[0028] R1, R2, and R3 are each independently selected from one of hydrogen, substituted or unsubstituted C1-C10 alkyl, substituted or unsubstituted C1-C10 ester, substituted or unsubstituted pyrimidinyl, or substituted or unsubstituted triazolopyrimidinyl.

[0029] The substituted group comprises at least one of hydroxyl, phenyl, amino, halogen, alkylthio, siloxane, and fluorobenzene-substituted cyclopropane.

[0030] In this embodiment of the invention, the compound of formula (A) contains an alkoxy group, a nitrogen atom, and a dioxacyclopentyl group. The alkoxy group facilitates coordination between formula (A) and lithium ions, thereby regulating the solvation structure of lithium ions and changing the interfacial transport impedance. The nitrogen atom can participate in the film formation process to form an interfacial passivation film on the negative electrode side, improving the ionic conductivity of the passivation film and enhancing the ion transport capability of the negative electrode, thus significantly improving its application performance in fast charging and low-temperature scenarios. The dioxacyclopentyl group is more likely to undergo ring-opening reactions, increasing the content of inorganic salts in the passivation film on the electrode surface, reducing the thickness of the SEI, increasing the lithium ion permeability in the passivation film, reducing the risk of electrode leakage, and thus improving cycle stability. In addition, because the nitrogen atom and alkoxy group are electron-rich groups, they are more likely to combine with lithium ions, thereby entering the solvation shell and moving with the lithium ions to the negative electrode surface, which enhances the film formation capability of the compound of formula (A). Therefore, the addition of compound (A) in the embodiments of the present invention can form a passivation film with low impedance and stability on the surfaces of the positive and negative electrodes, respectively, suppressing the increase of interfacial impedance and electrolyte decomposition, thereby improving the stability of the battery under low temperature cycling.

[0031] In some embodiments of the present invention, the dioxacyclopentyl group comprises cyclopentanol 1,3-dioxacyclopentyl.

[0032] In some embodiments of the present invention, the structure of the compound of formula (A) comprises at least one of formulas (A1) to (A9):

[0033]

[0034]

[0035] In one embodiment of the present invention, based on the total mass of the electrolyte, the mass percentage of the compound of formula (A) is 0.01% to 5.0%. The content of the compound of formula (A) is within the range of the present invention, which can form a stable passivation film on the surface of the positive and negative electrodes, effectively improving the low-temperature cycle performance and fast charging performance of the battery.

[0036] In some embodiments of the present invention, the mass percentage of the compound of formula (A) is preferably 0.05% to 3% based on the total mass of the electrolyte.

[0037] In some embodiments of the present invention, the electrolyte includes at least one selected from vinylene carbonate (VC), fluoroethylene carbonate (FEC), 1,3-propenesulfonate lactone (PST), and 1,3-propanesulfonate lactone (PS). The above substances work synergistically with the compound of formula (A) to suppress battery gas production and improve battery safety performance.

[0038] In some embodiments of the present invention, the electrolyte can be used normally in low-temperature environments ranging from -30°C to 25°C.

[0039] In one embodiment of the present invention, the electrolyte comprises a lithium salt, the concentration of which is 0.5M to 2M. The electrolyte provided by the present invention has a lithium salt concentration of 0.5M to 2M, which not only results in a suitable electrolyte viscosity and excellent conductivity, but also provides sufficient lithium electrons to coordinate with formula (A) in the electrolyte, fully utilizing the effect of formula (A), effectively regulating the solvation structure of lithium ions, and changing the interfacial transport impedance.

[0040] In one embodiment of the present invention, the lithium salt comprises lithium hexafluorophosphate (LiPF6). In another embodiment of the present invention, the electrolyte further comprises a lithium salt, wherein the lithium salt comprises at least one selected from lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiBOB), lithium difluorooxalate borate (LiDFOB), lithium difluorodioxalate phosphate (LiDFOP), lithium tetrafluorooxalate phosphate (LiOTFP), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0041] In one embodiment of the present invention, the electrolyte further comprises lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. Lithium hexafluorophosphate has a moderate ion transference number, a moderate dissociation constant, good antioxidant properties and good aluminum foil passivation ability in non-aqueous organic solvents, and can be matched with various positive and negative electrode materials. Lithium bis(fluorosulfonyl)imide has high electrolytic conductivity and good hydrolytic stability, which is beneficial to improving the rate performance and stability of the battery.

[0042] In some embodiments of the present invention, the organic solvents mentioned above include at least one of propylene carbonate, ethylene carbonate, butene carbonate, diethyl carbonate, dimethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl formate, methyl propionate, diphenyl ether, dimethyl sulfoxide, and sulfolane.

[0043] The present invention also proposes a secondary battery, which includes a positive electrode, a negative electrode, and an electrolyte as described above.

[0044] In some embodiments of the present invention, the positive electrode sheet includes a positive electrode active material, the positive electrode active material includes a nickel-cobalt-manganese material, and the nickel-cobalt-manganese material includes Li a Ni x Co y Mn z M eO2, wherein 0.9≤a≤1.1, 0≤e≤0.1, 0.3≤x<1.0, 0<y<0.4, 0.1<z<0.4, x+y+z=1.0, and M contains at least one of Al, Zr, Sr, Ti, B, Mg, Sn, W, Y, Ba, Nb, Mo, Ta, Si, La, Er, Nd, Gd, and Ce.

[0045] In some embodiments of the present invention, the negative electrode sheet includes a negative electrode active material, which includes at least one of silicon carbide negative electrode material, graphite, or hard carbon.

[0046] In some embodiments of the present invention, the negative electrode sheet further includes a conductive agent and a binder; optionally, the conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, and graphene, and the binder includes carboxymethyl cellulose-based binders and resin-based binders.

[0047] In some embodiments of the present invention, the carboxymethyl cellulose-based adhesive includes at least one of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose; and / or the resin-based adhesive includes at least one of styrene-butadiene rubber, polyacrylic acid, and polyacrylonitrile.

[0048] In some embodiments of the present invention, the negative electrode sheet is prepared as follows: the components used to prepare the negative electrode sheet, such as the negative electrode active material, binder and conductive agent, are dispersed in a solvent such as deionized water to form a negative electrode slurry; the negative electrode slurry is coated on both sides of a negative electrode current collector such as copper foil; after baking, rolling, cutting and other processes, the negative electrode sheet can be obtained.

[0049] In some embodiments of the present invention, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector, wherein the compaction density of the positive active material layer is 1.6 g / cm³. 3 ~2.8g / cm 3 In some embodiments, the compaction density of the positive electrode active material layer can be 1.8 g / cm³. 3 ~2.5g / cm 3 In some embodiments, the compaction density of the positive electrode active material layer can be 2.0 g / cm³. 3 ~2.2g / cm 3 The compaction density of the positive electrode active material layer is within the range of this invention, which is beneficial for improving the battery capacity and specific energy.

[0050] In some embodiments of the present invention, the areal density of the positive electrode active material layer is 260 g / m². 2 ~330g / m 2In some embodiments, the areal density of the above-mentioned positive electrode active material layer is 280 g / m³. 2 ~310g / m 2 In some embodiments, the areal density of the above-mentioned positive electrode active material layer is 290 g / m³. 2 ~300g / m 2 .

[0051] In some embodiments of the present invention, the positive electrode further includes a conductive agent, which includes at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, hard carbon, carbon fiber, and carbon microspheres.

[0052] In some embodiments of this invention, the positive electrode sheet further includes an adhesive, which includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0053] In some embodiments of the present invention, the positive electrode sheet is prepared as follows: the components used to prepare the positive electrode sheet, such as the positive active material including the above-mentioned positive electrode material, binder and conductive agent, are dispersed in a solvent such as N-methylpyrrolidone to form a positive electrode slurry; the positive electrode slurry is coated on a positive electrode current collector such as aluminum foil; after drying, rolling, die cutting and other processes, the positive electrode sheet can be obtained.

[0054] Understandably, the secondary battery provided in the embodiments of the present invention also includes a separator.

[0055] In practical applications, the negative electrode sheet, separator and positive electrode sheet are stacked in sequence and wound to obtain a core. The core is then packaged to obtain a bare cell. After baking, the bare cell is injected with electrolyte, formed, resealed and sorted to obtain the above-mentioned secondary battery.

[0056] The secondary battery provided in this embodiment of the invention has a charging cutoff voltage of 4.2V to 4.8V.

[0057] The present invention also proposes an electrical device, wherein the aforementioned secondary battery is provided as the power supply for the electrical device.

[0058] The above-described secondary battery embodiments and electrical equipment embodiments include the electrolyte and achieve the same technical effect. To avoid repetition, they will not be described again here. For relevant details, please refer to the description of the electrolyte embodiments.

[0059] The present invention will be described in detail below through embodiments.

[0060] Performance testing methods

[0061] (1) Room temperature DCR test: At 25±2℃, charge the battery to 3.9V at 1C, then discharge at 1C capacity for 30min, adjust to 50% SOC, then pulse discharge at 10C constant current for 10s, adjust to 50% SOC according to the above method, and then charge for 10s. Calculate DCR = (voltage before pulse discharge - voltage after pulse discharge) / discharge current * 100%.

[0062] (2) Room temperature cycle performance test: At 25±2℃, the battery was charged and discharged at a charge and discharge rate of 0.33C / 0.33C in the range of 2.5 to 4.2V. The discharge specific capacity of the battery in the first cycle and the discharge specific capacity after 500 cycles were recorded. The capacity retention rate after 500 cycles was calculated as: discharge specific capacity after 500 cycles / discharge specific capacity in the first cycle * 100%.

[0063] (3) Low temperature cycle performance test: At -10℃, the battery is charged and discharged at a rate of 0.33C / 0.33C within the range of 2.5 to 4.2V. The discharge specific capacity of the battery in the first cycle and the discharge specific capacity after 500 cycles are recorded. The capacity retention rate after 500 cycles is calculated as: discharge specific capacity after 500 cycles / discharge specific capacity in the first cycle * 100%.

[0064] Example 1

[0065] (1) Preparation of electrolyte:

[0066] At room temperature, in a glove box filled with argon (H2O < 1 ppm, O2 < 1 ppm), EC, EMC, and DEC are mixed evenly in a mass ratio of 3:5:2. Lithium salts are added to the resulting mixed solvent in batches and stirred evenly. Then, A5, equivalent to 0.01% of the total mass of the electrolyte, is added and stirred evenly to obtain the electrolyte.

[0067] (2) Preparation of positive electrode sheet

[0068] The positive electrode active material Li(Ni) 0.8 Mn 0.1 Co 0.1 O2 (NMC811), conductive agent acetylene black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of NMC811:Super P:PVDF = 94:3:3, and then evenly dispersed in 1-methyl-2-pyrrolidone (NMP) to form a uniform black slurry. The mixed black slurry is coated on both sides of aluminum foil, and after baking, rolling, and cutting, the positive electrode sheet is obtained.

[0069] (3) Preparation of negative electrode sheet

[0070] The negative electrode active material graphite, conductive agent acetylene black (Super P) and binder SBR are mixed evenly in a mass ratio of 94:3:3 and then evenly dispersed in deionized water to form a uniform black slurry. The mixed slurry is coated on both sides of copper foil, and then baked, rolled, and cut into sheets to obtain the negative electrode sheet.

[0071] (4) Preparation of lithium-ion batteries

[0072] The prepared positive electrode sheet, separator (PP separator), and negative electrode sheet are stacked in sequence, with the separator in the middle of the positive and negative electrode sheets. After winding, hot pressing and shaping, and electrode tab welding, a bare cell is obtained. The bare cell is placed in an outer packaging aluminum-plastic film and baked in an oven at 85±10℃ for 24 hours. The electrolyte prepared above is injected into the dried battery, and the battery is allowed to stand, form, and be capacity tested to complete the preparation of the lithium-ion soft pack battery.

[0073] The preparation methods for the remaining embodiments and comparative examples are the same as those in Example 1, with differences shown in Table 1.

[0074] Table 1

[0075]

[0076]

[0077] The batteries prepared in each embodiment and comparative example were subjected to room temperature DCR test, room temperature cycle performance test, and low temperature cycle performance test. The test data are shown in Table 1.

[0078] The experimental results from Examples 1-24 and Comparative Example 1 show that adding a compound with the structure shown in Formula A can reduce the initial internal resistance of the battery and the increase in internal resistance during cycling, thereby improving the capacity retention rate during room temperature cycling and low temperature storage.

[0079] The experimental results of Examples 1 to 7 show that as the content of A5 in the electrolyte increases, the generated interfacial film becomes denser, which has a beneficial effect on suppressing the increasing trend of battery internal resistance and volume expansion rate during cycling and reducing irreversible losses during storage. However, excessive use of A5 results in a significant increase in initial impedance, which is not conducive to the dynamic performance of the battery. Therefore, the preferred mass percentage of A5 in the electrolyte is 0.05% to 3%.

[0080] As demonstrated in Examples 8 and 16-17, both the compaction density and areal density of the positive electrode active material layer in the positive electrode sheet affect the stability of the positive and negative electrode interface film, thereby affecting the cycle performance of the battery. Specifically, the compaction density of the positive electrode active material layer is 1.6 g / cm³. -3 ~2.8g / cm -3 The surface density is 260 g / cm³. -3~330g / m 2 At that time, the battery's DCR change rate is lower and its low-temperature cycle performance is particularly good.

[0081] In summary, in this embodiment, the electrolyte includes a compound having formula (A), which contains an alkoxy group, a nitrogen atom, and a dioxane-pentyl group. The alkoxy group facilitates coordination between formula (A) and lithium ions, thereby regulating the solvation structure of lithium ions and altering the interfacial transport impedance. The nitrogen atom helps form a high lithium-ion permeability interfacial film on the negative electrode side, improving the ion transport capability of the negative electrode and significantly enhancing its performance in fast charging and low-temperature scenarios. The dioxane-pentyl group is more prone to ring-opening reactions. Therefore, the addition of formula (A) can form low-impedance and stable passivation films on the surfaces of the positive and negative electrodes, respectively, suppressing the increase in interfacial impedance and electrolyte decomposition, thereby improving the stability of the battery during low-temperature cycling. This solves the problems of lithium plating, polarization, and high passivation film impedance at the electrodes that are common in existing lithium-ion batteries at low temperatures.

[0082] Although preferred embodiments of the present invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present invention.

[0083] The electrolyte, secondary battery, and electrical device provided by the present invention have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. An electrolyte, characterized in that, The compound includes a compound of formula (A), wherein the compound of formula (A) includes at least one of compounds of formulas (A1) to (A9):

2. The electrolyte according to claim 1, characterized in that, Based on the total mass of the electrolyte, the mass percentage of the compound of formula (A) is 0.01% to 5%.

3. The electrolyte according to claim 1, characterized in that, Based on the total mass of the electrolyte, the mass percentage of the compound of formula (A) is 0.05% to 3%.

4. The electrolyte according to claim 1, characterized in that, The electrolyte also includes at least one of vinylene carbonate, fluorovinyl carbonate, 1,3-propenesulfonate lactone, and 1,3-propanesulfonate lactone.

5. A secondary battery, characterized in that, It includes a positive electrode, a negative electrode, and an electrolyte as described in any one of claims 1 to 4.

6. The secondary battery according to claim 5, wherein the positive electrode sheet comprises a positive electrode active material, the positive electrode active material comprises a nickel-cobalt-manganese material, and the nickel-cobalt-manganese material comprises Li a Ni x Co y Mn z M e O2, where, 0.9≤a≤1.1, 0≤e≤0.1, 0.3≤x<1.0, 0<y<0.4, 0.1<z<0.4, x+y+z=1.0, and M contains at least one of Al, Zr, Sr, Ti, B, Mg, Sn, W, Y, Ba, Nb, Mo, Ta, Si, La, Er, Nd, Gd, and Ce.

7. The secondary battery according to claim 5, characterized in that, The positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector, wherein the compaction density of the positive active material layer is 1.6 g / cm³. 3 ~2.8 g / cm 3 .

8. The secondary battery according to claim 5, characterized in that, The areal density of the positive electrode active material layer is 260 g / cm³. 2 ~330 g / m 2 .

9. An electrical appliance, characterized in that, The device includes the secondary battery as described in any one of claims 5 to 8, wherein the secondary battery serves as the power supply for the electrical equipment.

Citation Information

Patent Citations

  • Nonaqueous electrolyte solution, electrochemical element using same, and 1,2-dioxypropane compound used in same

    CN102782927A

  • Electrolyte for lithium-sulfur battery and lithium-sulfur battery comprising same

    CN116391283A